Effect of filler wire properties on porosity formation in laser welding of AC-170PX aluminium alloy for lightweight automotive component manufacture. (May 2017) - AlShaer, Ahmad Wael; Li, Lin; Mistry, Anil
AC-170PX (AA6014) alloys are typically used in lightweight automobile vehicles. Laser welding can be a viable tool for the assembly of components. However, porosity is often generated during aluminium welding. In this article, an investigation is reported on the characteristics of porosity formation in high-power disc laser welding of AC-170PX aluminium alloy sheets in two weld joint configurations: fillet edge and flange couch with three different filler wires of 4xxx, 3xxx and 5xxx aluminium series for each joint. Porosity, microstructures, tensile strengths and joint geometry were investigated. It has been found that the use of filler wires with higher Mg and Mn content such as AA5083 and AA3004 leads to a significant reduction in porosity to less than 1.5% in both types of joints compared with up to 80% porosity with the silicon-rich AA4043 wire. The mechanism that led to this improvement is discussed.